Characterization of Fatty Acid Metabolism-Related Genes Landscape for Predicting Prognosis and Aiding Immunotherapy in Glioma Patients - Jiang, Feng; Luo, Fei; Zeng, Ni; Mao, Yan; Tang, Xinfang; Wang, Jimei; Hu, Yifang; Wu, Chuyan (Frontiers in Immunology, 2022)
Glioma is a highly malignant brain tumor with a poor survival rate. The involvement of fatty acid metabolism in glioma was examined in order to find viable treatment options. The information was gathered from the Cancer Genome Atlas (TCGA) and the Chinese Glioma Genome Atlas (CGGA) databases. A prognostic signature containing fatty acid metabolism dependent genes (FAMDs) was developed for predicting outcome of glioma by multivariate and least absolute shrinkage and selection operator (LASSO) regression analyses. In the TCGA cohort, individuals with a good score had a worse prognosis than those with a poor score, which was validated in the CGGA cohort. Higher risk individuals were more susceptible to crizotinib, according to further research by "pRRophetic" R package. High-risk individuals were eligible for activating immune cell associated receptor pathway, according to a complete study of the connection between predictive risk rating model and tumor microenvironment (TME) features. We also discovered that anti-PD-1/PD-L1 and anti-CTLA4 immunotherapy are more effective in high-risk individuals. Furthermore, we demonstrated that CCNA2 promotes glioma proliferation, migration and invasion, and regulates macrophage polarization. Therefore, examining fatty acid metabolism pathway aids our understanding on TME invasion properties, allowing us to develop more effective immunotherapies for glioma.